The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1038/tp.2013.101
|View full text |Cite
|
Sign up to set email alerts
|

Duplications in RB1CC1 are associated with schizophrenia; identification in large European sample sets

Abstract: Schizophrenia (SCZ) is a severe and debilitating neuropsychiatric disorder with an estimated heritability of ~80%. Recently, de novo mutations, identified by next-generation sequencing (NGS) technology, have been suggested to contribute to the risk of developing SCZ. Although these studies show an overall excess of de novo mutations among patients compared with controls, it is not easy to pinpoint specific genes hit by de novo mutations as actually involved in the disease process. Importantly, support for a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…First, SETD1A Takata et al, 2016) is the most significant gene across analyses (FDR ∼ 1.5×10 −3 ), TAF13 is also significant across analyses. Of two genes with FDR < 0.1, RB1CC1 was reported in a study of copy-number variation in SCZ (Degenhardt et al, 2013). Second, we found substantial overlap of top genes in this study and gene sets known from previous reports on these same SCZ data Genovese et al (2016).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…First, SETD1A Takata et al, 2016) is the most significant gene across analyses (FDR ∼ 1.5×10 −3 ), TAF13 is also significant across analyses. Of two genes with FDR < 0.1, RB1CC1 was reported in a study of copy-number variation in SCZ (Degenhardt et al, 2013). Second, we found substantial overlap of top genes in this study and gene sets known from previous reports on these same SCZ data Genovese et al (2016).…”
Section: Discussionsupporting
confidence: 63%
“…SETD1A has been confirmed as the highest statistically significant gene of SCZ in previous studies Takata et al, 2016), while TAF13 was only reported as a potential risk gene in the study of . Interestingly for the RB1CC1 gene, rare duplications were reported to be associated with SCZ with very high odds ratio (8.58) in the study of Degenhardt et al (2013), but has not been reported in other studies since. In addition, as discussed by the authors, duplications at this gene were also observed by Cooper et al (2011) with an odds ratio = 5.29 in a study of 15,767 children with ID and/or DD.…”
Section: Rare Variant Genetic Architecture Of Sczmentioning
confidence: 77%
See 1 more Smart Citation
“…We found that SETD1A [ 8 , 25 ] is the most significant gene across analyses (FDR ∼1.5×10 −3 ), and that TAF13 [ 6 ] is FDR significant. Of two genes with 0.05< FDR <0.1, rare duplications covering RB1CC1 have been reported in SCZ [ 78 ] and in ID and/or DD [ 79 ]. Two novel conserved non-coding motif gene sets showing brain-specific expression [ 73 ] were enriched (Additional file 1 : Table S20), including targets of the transcription factor MAZ and of microRNAs MIR10A/B.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of such duplications on RB1CC1 gene expression has never been evaluated in CNV carriers and, since partial gene duplications of RB1CC1 have also been documented in schizophrenic subjects, it is unproved whether the pathomechanism is mediated by haploinsufficiency due to gene disruption rather than genuine overexpression of the gene. Notably, Degenhardt et al (2013) reported full RB1CC1 duplication in three SCZ patients, partial gene duplication in five patients, and a duplication immediately upstream of the RB1CC1 gene in an additional patient. Importantly, all partial gene duplications were detected by chromosomal microarray only without breakpoint‐level analysis, which is essential to interpret their effects on gene structure in terms of orientation, location, and possible alteration of the reading frame causing loss‐of‐function.…”
Section: Discussionmentioning
confidence: 99%